2017
DOI: 10.1002/jbmr.3240
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Deficits in Cortical Bone Density, Microarchitecture, and Bone Size: Framingham HR-pQCT Study

Abstract: Older adults with type 2 diabetes (T2D) tend to have normal or greater areal bone mineral density (aBMD), as measured by DXA, than those who do not have diabetes (non-T2D). Yet risk of fracture is higher in T2D, including 40% to 50% increased hip fracture risk. We used HR-pQCT to investigate structural mechanisms underlying skeletal fragility in T2D. We compared cortical and trabecular bone microarchitecture, density, bone area, and strength in T2D and non-T2D. In secondary analyses we evaluated whether associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
126
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(147 citation statements)
references
References 58 publications
13
126
2
Order By: Relevance
“…Bone material strength index by reference point indentation was lower in women with type 2 diabetes compared with leaner non‐diabetic women . In the Framingham HR‐pQCT Study, patients with type 2 diabetes had lower cortical volumetric BMD, higher cortical porosity and smaller cross‐sectional area at the tibia . These structural deficits may contribute to fracture risk in type 2 diabetes.…”
Section: Methodsmentioning
confidence: 95%
“…Bone material strength index by reference point indentation was lower in women with type 2 diabetes compared with leaner non‐diabetic women . In the Framingham HR‐pQCT Study, patients with type 2 diabetes had lower cortical volumetric BMD, higher cortical porosity and smaller cross‐sectional area at the tibia . These structural deficits may contribute to fracture risk in type 2 diabetes.…”
Section: Methodsmentioning
confidence: 95%
“…Several studies have demonstrated that individuals with T2DM have normal or increased trabecular bone, yet compromised cortical bone compared with controls . Compromised cortical bone structure includes cortical porosity, which can be quantified using advanced imaging modalities such as high‐resolution pQCT (HR‐pQCT) .…”
Section: Discussionmentioning
confidence: 99%
“…This is because the precision of this scanning modality is affected by tissue depth (eg excess fat mass) . Also, DXA cannot distinguish between trabecular and cortical bone, which may be disproportionately affected in insulin‐resistant individuals . Three‐dimensional imaging technology such as peripheral quantitative computed tomography (pQCT) may be a more informative tool to understand the relationship between insulin resistance and determinants of bone quality in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the association between diabetes and bone metabolism has achieved wide attention. Researchers observed that older adults with type 2 diabetes tended to have normal or greater BMD than those without diabetes (31). For instance, Oei et al (32) found that poor glycemic control in those with type 2 diabetes was associated with a high BMD in narrower bones.…”
Section: Discussionmentioning
confidence: 99%